Management of Anemia in Cancer Patients (Anwer Khan Modern Medical College Journal, 2020)
Anemia is a frequent complication in cancer patients. Cancer-related anemia adversely affects quality of life and is associated with reduced overall survival. Reasons for anemia in cancer patients are decreased production of RBCs resulting from nutritional deficiencies; insufficient production of RBCs because of the presence of chronic disease; Cancer promotes inflammatory cytokine production, which suppresses erythropoiesis and erythropoietin (EPO) production; bone marrow infiltration by the tumor or bone marrow suppression resulting from anticancer treatment such as surgery, chemotherapy, or radiotherapy; and increased loss of RBCs caused by blood loss from the tumor, surgery, or hemolysis. Correction of anemia can be achieved by different methods.Treatment is aimed at increasing the oxygen-carrying capacity of the blood, reducing fatigue, and improving the patient's overall quality of life. Erythropoiesisstimulating agents, iron supplementation, and red blood cell transfusions have all been recommended in different settings.Anwer Khan Modern Medical College Journal Vol. 11, No. 1: Jan 2020, P 66-72